1993
DOI: 10.1016/0266-7681(93)90189-m
|View full text |Cite
|
Sign up to set email alerts
|

Improved Results in Zone 2 Flexor Tendon Injuries with a Modified Technique of Immediate Controlled Mobilization

Abstract: The results following primary and delayed primary repair in zone 2 flexor tendon injuries were evaluated in 85 fingers of 79 patients using immediate controlled mobilization post-operatively. In 31 patients a conventional Kleinert technique was used. In the remaining 48 patients a modified technique was used with rubber band traction to all fingers instead of only to the injured one. Also a shorter dorsal splint was used in order to secure extension of the PIP and DIP joints. The results were improved and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…However, there have been some problems in active flexion mobilisation, tendon rupture and strict management under the supervision of experienced hand specialists. 3,6,11,16 Concerning early passive flexion exercise, some authors have reported no differences between patients with static or dynamic splinting, 12 but many authors believe early passive motion contribute to greater range of motion. Percival et al 14 reported that 60% of cases treated with dynamic splint were rated as satisfactory, and 44% of cases treated with immobilisation were rated as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been some problems in active flexion mobilisation, tendon rupture and strict management under the supervision of experienced hand specialists. 3,6,11,16 Concerning early passive flexion exercise, some authors have reported no differences between patients with static or dynamic splinting, 12 but many authors believe early passive motion contribute to greater range of motion. Percival et al 14 reported that 60% of cases treated with dynamic splint were rated as satisfactory, and 44% of cases treated with immobilisation were rated as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Several hand surgeons have advocated postoperative active flexion protocols. 3,11,16 With regard to flexor pollicis longus (FPL) tendon repair, some authors have reported that results obtained with an early exercise protocol (passive flexion and active extension exercise) are superior to those with immobilisation, while others have reported no difference between the two methods. 4,12,14 It has been reported that results after FPL tendon repair are significantly affected by the following factors: age at injury, type of injury, zone of injury, time elapsed from injury to surgery, and postoperative management.…”
Section: Introductionmentioning
confidence: 99%
“…The functional outcome for the tendon injuries in zone 2 are worst in view of more chances of adhesions formation 14. Before repairing the tendon it is essential to ascertain other possible injuries which include fracture of the phalanx and metacarpal, as well as the neurovascular damage to the involved digit.…”
Section: Acute Flexor Tendon Injuriesmentioning
confidence: 99%
“…After the sixth week, patients are allowed to gradually increase load toward unrestricted activity at 8 weeks. 43,46 New Developments Recently, early active motion protocols have been developed in response to experimental and clinical studies that demonstrate beneficial effects of early active motion (protocol outline is presented in Table 4). 47,48 The hypothesis is that early controlled active mobilization may actually improve differential gliding between the flexor digitorum profundus and flexor digitorum superficialis tendons and improve tendon excursion.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…However, systematic reviews of the literature have not been able to find evidence from randomized controlled trials to define the best mobilization strategy 41 Rehabilitation can be successfully initiated in the first days after surgery, with or without rubber traction bands. [43][44][45] Common for all protocols is that the patients are immobilized in a dorsal plaster splint with the wrist in 30 degrees of flexion and the metacarpophalangeal joints in 70 degrees of flexion. The passive flexion-active extension protocol is typically maintained for 4 weeks, followed by active flexion and extension without load for an additional 2 weeks.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%